PENGEMBANGAN MEDIA ANIMASI KOMPUTER UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD UNGGULAN MUSLIMAT NU KABUPATEN KUDUS - Widiastuti, Nur Aeni (Jurnal DISPROTEK, 2018)
The success of a learning process influenced by teachers, learning materials, media and student. The problem of this research is developing Media Computer Animation How to improve student learning outcomes in class V Elementery School of Muslimat NU Kudus. Computer animation as a medium of instruction in intermediate teachers deliver the message because the use of this software is more practical, efficient, can be self-learning and also have some educational value, such as: 1) Can be visualized, 2) to overcome the limitations of space and time, 3) Can reduce verbal. This study aims to determine improving student learning outcomes in English language learning. This research uses classroom action research conducted in two cycles. In the first ,which in practice only teachers use classroom action research methods and not using the media increased by 5.4 from the pretest 12.36 and posttest 17.76. Then in the second which in its implementation with a class action research methods and using computer animation media also increase 4.11 from pretest 21 and postest 25.11. As for the observation of the first cycle included into the category of less and the second cycle included good categories